Studi Manajemen Pertahanan dari Sisi Teori dan Praktik: Perkembangan dan Penerapan di Indonesia - Endro Tri Susdarwono (Fakultas Ekonomi dan Bisnis Universitas Nasional, 2022)
Defense management is always related to the success and or failure of a country in order to manage its national resources with the aim of becoming a national power. The purpose of this study is to provide a description of defense management in terms of theory and practice in its development and application in Indonesia. The approach in this study uses a descriptive approach, while the type of research is descriptive qualitative research, namely describing and interpreting what exists, it can be about existing conditions/relationships. Opinions that are growing, processes that are ongoing, consequences / effects that occur or trends that are developing. The problem of transparency and accountability in the implementation of the functions of defense institutions starts from the basics to lead to civil oversight of the decision-making process and defense performance. Defense management is considered a suprasystem of the three defense management subsystems consisting of: a resource management system, a management system for the development/strength/capability of state defense, and a management system for the use of force/capability of state defense and security.